- - Manzini, Jorge Luis (Acta Bioethica, 2000)
This paper consists in a particularised analysis of the Declaration of Helsinki, revised at the 52nd WMA General Assembly at Edinburgh in October 2000. The framework was as follows: 1) an introduction to the subject 2) a general consideration about formal and substantial aspects of the changes 3) a detailed analysis of every modified article, be it a change or an addition; and the comparison, when appropiate, between the Spanish and the English versions of the Declaration. This plan was developed by means of XXV "Commentaries" interpolated along the transcription of the Declaration, as was available from the WMA website, www.wma.net/s/helsinki.html, on November 28, 2000. The phrases and paragraphs analysed are identified by means of different printing characters for the modified and new pieces, and the English version. The analysis was made from a bioethical perspective, especially regarding Human Rights concerns, as well as considering the scientific issues of medical research, including the viewpoint of Evidence based Medicine. Conclusions: 1) all of the amendments strengthen the Declaration, advocating for higher respect for the Human Rights of research subjects. 2) a further revision of the formal aspects (language) of the Spanish version would be advisable, because of its many punctual weaknesses and ambiguities, as compared with the English version.